Nano-priming: Impression on the beginner of plant life - Nidhi Kandhol; Vijay Pratap Singh; Naleeni Ramawat; Rajendra Prasad; Devendra Kumar Chauhan; Shivesh Sharma; Renato Grillo; Shivendra Sahi; José Peralta-Videa; Durgesh Kumar Tripathi (Plant Stress, 2022)
In the interest to assist plant growth and bolster their strength to deal with the environmental cues, priming has been revealed to play a remarkable role through induction of several metabolic and physiological alterations. It can be delineated as a physiological process of prompting plants by treating with biological/chemical priming agents or mild stress to display better growth biomarkers and stress resistance in case of repeated stress encounters. Priming of seeds has been of great interest for researchers in recent years which brings about changes in seed metabolism to support the successful establishment of plants in its environment through faster and more prominent seed germination and growth of developing seedlings. The conspicuously displayed rise in applications of nanotechnology in agriculture has also stirred up the research on nano-priming of plants. Nanoparticles (NPs) have appeared to be more proficient in influencing growth, quality, yield, and reactive oxygen species (ROS) homeostasis in plant seeds than other methods of priming such as priming with the bulk materials or hydro-priming. However, there is a need to opt-out NPs exhibiting toxic effects on seed germination and seedling growth for deliberate priming while understanding their possible repercussions on plant as well as human health. Therefore, this article aims to present the recent research conducted in the field of nano-priming of seeds of different plants along with recommendations for future research.